Paciente de sexo femenino de 83 años de edad con insuficiencia renal aguda, ùlcera antral péptica y diabetes mellitus tipo 2 - Valero Suárez, Génesis Cariddys (2020)
The present clinical case is about an 83-year-old female patient with acute renal failure, peptic antral ulcer and type II diabetes mellitus. The clinical examination was performed on the patient who was treated at the General of the North of Guayaquil IESS Ceibos. The work arises through the interest of studying the relevance that these pathologies have in the elderly and in this way establish new ways of quality of life and at the same time be able to obtain a better response to the treatment, avoiding the possible complications that originate and that way to be able to diminish the impact that these diseases have since it affects on a way the socio-economic aspect of the family. At the same time it will serve as a guide to raise awareness among people suffering from diabetes and high blood pressure so that they go to specialized centers where they can receive a better quality of care, and therefore these pathologies can be detected in time, guaranteeing a longer life span and decreasing morbidity and mortality due to these diseases in older adults. In conclusion, it was determined that older adults are more likely to suffer from these pathologies due to the physiological changes of their own age, to which the acquired food uncultured is added.